Landscape Protection and Development in the Firtos Region: Experiences of an International Students' Project - Sallay, Ágnes; Drexler, Dóra; Gnadinger, Johannes; Heinemann, Thomas (4D Journal of Landscape Architecture and Garden Art, 2006)
The Department of Landscape Planning and Regional Development of the Corvinus University of Budapest, the Landscape Ecology Department of the Technical University of Munich and the Sapientia University in Csíkszereda coilaborate since 2005 in the establishment of a landscape development plán for the Firtos Region. The Firtos Region has an area of app. 500 square kilometres. It lies in the Sekler Land in Transylvania, Románia, on the border of the counties Maros and Hargita, around the Firtos Mountain.
Keywords: developement; students' project